Family Roles in the Process of Adaptation CVA Patients With Mobilization Physical Disorders by Callista Roy Theory - HR, Hakim Tobroni; Kai, Meggy Wulandari; Fudali, Ahmad; Susanti, Novia; Alkatiri, Wardah (International Journal of Psychosocial Rehabilitation, 2020)
CVA is a disease that causes physical weakness. This condition makes CVA patients need a family role to adapt. Calista Roy proposed a theory about the process of adaptation. The purpose of this study was to determine family roles in the process of adaptation CVA patients with mobilization physical disorders by Callista Roy theory. The research design was correlational with cross sectional approach. The population was CVA patients with disorders physical mobilization total of 147 patients with a sample of 60 respondents, taken by accidental sampling technique. Independent variables are the role of the family and the dependent variable is the process of adaptation. Data processing techniques are then cross tabulated using the chi-square test with contingency coefficients. The survey results from respondents have a family role with a high role category of 30 respondents (50%), which can adapt 48 respondents (80%). The results of data analysis with chi-square test p = 0.003, then H0 is rejected, meaning that there is a relationship between the two variables with the level of moderate and positive relationship (contingency coefficient: 0.407). so the role of the family is to accelerate the process of adaptation.